2019
DOI: 10.3390/met9111195
|View full text |Cite
|
Sign up to set email alerts
|

Damping Capacity and Storage Modulus of SiC Matrix Composites Infiltrated by AlSi Alloy

Abstract: In this paper, we describe how an aluminum alloy-reinforced silicon carbide ceramic matrix composite (SiCCMC) with excellent damping capacity and storage modulus was fabricated by infiltration. The effects of silicon (Si) on the microstructure and damping capacity of the composite were studied. The interface bonding and damping mechanism involved were also discussed. The results show that composites with high damping capacity can be obtained by infiltrating SiC ceramics with aluminum alloy. The residual Si in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…This mechanism appears somewhat inhibited for the Al-Zn reinforced with 8 wt.% Cu. The higher damping capacity in the Al-Zn composite reinforced 8 wt.% SiC compared with the composite composition reinforced containing 8 wt.% Cu, can be linked to dislocation damping and the intrinsic damping phenomena exhibited by multiphase systems (in this case, the matrix and reinforcements) [10]. Silva Prasad et al [19] reported that SiC powder has damping capacity higher than that of Ferrous based metallic reinforcements.…”
Section: Damping Behaviourmentioning
confidence: 97%
See 2 more Smart Citations
“…This mechanism appears somewhat inhibited for the Al-Zn reinforced with 8 wt.% Cu. The higher damping capacity in the Al-Zn composite reinforced 8 wt.% SiC compared with the composite composition reinforced containing 8 wt.% Cu, can be linked to dislocation damping and the intrinsic damping phenomena exhibited by multiphase systems (in this case, the matrix and reinforcements) [10]. Silva Prasad et al [19] reported that SiC powder has damping capacity higher than that of Ferrous based metallic reinforcements.…”
Section: Damping Behaviourmentioning
confidence: 97%
“…Flat shaped rectangular bar samples with dimensions of 55 mm  5.0 mm  2.0 mm were machined for the test. The DMA which operates on three-point bending mode, generated data for storage modulus (dynamic modulus) (É) and loss modulus (Ë), which were used for analysis of the damping capacity (tan d) using equation ( 3) [10]. The analysis was performed at a strain amplitude (Ɛ) of 10 mm, vibration frequencies (f) of 1 Hz, temperature range (ƭ) of 30-200 °C, and heating rate (Ʈ) of 8 K/min.…”
Section: Damping Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 summarizes the Raman shifts observed in samples Ti20Al80 and Ti80Al20, along with their indexing. Raman Shift Indexing Ti20-AlSi [cm −1 ] Species Corroded Al Lightly-corroded Al Titanium AlCl4 -* , [a] 123 122 122 Silicon is characterized by a well-known specific peak at 520 cm −1 and a secondary peak of about 950 cm −1 [43,44]. Both peaks were found in Al corroded and lightly-corroded Al areas.…”
Section: Raman Spectramentioning
confidence: 99%
“…Silicon is characterized by a well-known specific peak at 520 cm −1 and a secondary peak of about 950 cm −1 [43,44]. Both peaks were found in Al corroded and lightly-corroded Al areas.…”
Section: Raman Spectramentioning
confidence: 99%